Lethality and Autonomous Systems: Survey Design and Results [Industry/Research News] (IEEE robotics & automation magazine, 2008)
When we consider the use of deadly force by robots, it is crucial that we ask the question, "What is acceptable?" As a part of an effort to "understand, define, and shape expectations regarding battlefield robotics?" Moshkina and Arkin conducted a survey of researchers, policymakers, military personnel, and the general public to ascertain the current point of view maintained by various demographic groups on this subject. As part of this study, the team conducted an online public opinion survey on the use of robots capable of lethal force in warfare. The main objective of the survey was to determine the level of acceptance by various demographic groups of the employment of potentially lethal robots in warfare as well as their attitudes toward related ethical issues.